ANALISIS LAJU TIMBUNAN DAN KOMPOSISI SAMPAH DI PERMUKIMAN PESISIR KENJERAN SURABAYA - Nita Citrasari; Nur Indradewi Oktavitri; Nuril A. Aniwindira (The East Java Biological Society, 2012)
Solid waste in Coastal Settlement Kenjeran Surabaya is alarming due to of the habit of the peoples to pile until 1 meter on surface coastal land. The habit can impact of environmental pollution to that area. So, the purpose of this research was to know the solid waste generation and the composition of solid waste in Coastal Settlement Kenjeran Surabaya. The methods used was weigth volume analysis. That result of research showed that the solid waste generation was 0.23 kg/person/day with the composition 76.21% of garbage, 10.83% of plastic, 5.33% of paper, 0.82% of glass, 1.21% of wood, 2.27% of fabric, 0.44% of metal, 0.08% of foam, and 2.58% of the others(soil, sand, and gravel). The solid waste generation and the composition of solid waste could be used for the planning of management in Coastal Settlement Kenjeran Surabaya.